NHCs in Asymmetric Organocatalysis: Recent Advances in Azolium Enolate Generation and Reactivity - Douglas, James; Churchill, Gwydion; Smith, Andrew D. (Synthesis, 2012)
Organocatalysis represents a synthetic paradigm that has grown exponentially in popularity over the last decade, arguably becoming one of the most desired synthetic methods for the creation of enantiomerically enriched products. Within this field the use of N-heterocyclic carbenes (NHCs) has seen appreciable research activity with the realisation of many novel reaction types. This review provides a comprehensive account of recent advances in the generation and reactivity of azolium enolates with exclusive focus on those processes rendered asymmetric through the use of chiral NHCs.1 Introduction: NHCs in Organocatalysis 1.1 Azolium Enolates2 Azolium Enolate Generation via Ketenes2.1 Asymmetric Formal [2+2] Cycloadditions 2.2 Asymmetric Formal [3+2] Cycloadditions 2.3 Asymmetric Formal [4+2] Cycloadditions 2.4 Asymmetric Protonation and Halogenation3 Azolium Enolate Generation via α-Functionalised Aldehydes 4 Azolium Enolate Generation via Enals 5 Activated Esters as Azolium Enolate Precursors 6 Conclusions and Outlook
Keywords: N-heterocyclic carbene; azolium enolate; organocatalysis, ketene; α-functionalised aldehydes; Enals; activated esters